Analysis of enteric nervous system and intestinal epithelial barrier to predict complications in Hirschsprung’s disease - Anne Dariel (Nature Portfolio, 2020)
Abstract In Hirschsprung’s disease (HSCR), postoperative course remains unpredictable. Our aim was to define predictive factors of the main postoperative complications: obstructive symptoms (OS) and Hirschsprung-associated enterocolitis (HAEC). In this prospective multicentre cohort study, samples of resected bowel were collected at time of surgery in 18 neonates with short-segment HSCR in tertiary care hospitals. OS and HAEC were noted during postoperative follow-up. We assessed the enteric nervous system and the intestinal epithelial barrier (IEB) in ganglionic segments by combining immunohistochemical, proteomic and transcriptomic approaches, with functional ex vivo analysis of motility and para/transcellular permeability. Ten HSCR patients presented postoperative complications (median follow-up 23.5 months): 6 OS, 4 HAEC (2 with OS), 2 diarrhoea (without OS/HAEC). Immunohistochemical analysis showed a significant 41% and 60% decrease in median number of nNOS-IR myenteric neurons per ganglion in HSCR with OS as compared to HSCR with HAEC/diarrhoea (without OS) and HSCR without complications (p = 0.0095; p = 0.002, respectively). Paracellular and transcellular permeability was significantly increased in HSCR with HAEC as compared to HSCR with OS/diarrhoea without HAEC (p = 0.016; p = 0.009) and HSCR without complications (p = 0.029; p = 0.017). This pilot study supports the hypothesis that modulating neuronal phenotype and enhancing IEB permeability may treat or prevent postoperative complications in HSCR.